Dealuminasi dan Karakterisasi Zeolite Y sebagai Katalis untuk Konversi Gliserol menjadi Glycerol Monolaurate - Didi Dwi Anggoro; Wahyu Bahari Setianto; Fadhil Rifqi P; Antonio Giovanno (Seminar Nasional Teknik Kimia Kejuangan, 2016)
Glycerol is a side product of a biodiesel production using transesterification process and an alcoholic compound that consists of three hydroxyl group. One of the glycerol derivative compound is Glycerol Monolaurate which used in food additives, surfactant, medicine, cosmetics and others. In the making of Glycerol Monolaurate, catalysts is used to accelerate the reaction and increasing the yield of Glycerol Monolaurate. One of the catalysts that had been used is Zeolite Y. Dealumination is used to increase the acidity of the zeolites. Characterizationis used to determine the characteristics of the Zeolit Y that had been dealuminise. This study consists of several stages, there are dealumination of Zeolite Y using H2SO4. Then, drying at 110 º C for 1 hour. Then, calcinating at 500-600 ºC for 3 hours. Catalyst characteristics are analyzing by the Surface Area Analyzer to determine the surface area of the catalyst, and analysis with X - Ray Diffraction (XRD) to identify the bulk phase and determine the nature of the catalyst crystals or crystalitation of a catalyst, and Temperature-Programmed Desorption (TPD) to analyze the acidity of Zeolit Y that had been dealuminise. So we can get the optimum condition to produce Zeolit Y catalysts which also can Glycerol Monolaurate with the biggest yield possible.